{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# hw1 - Granillo Yvette Homework 1 Due 3:00 am Inst Edward...

This preview shows pages 1–4. Sign up to view the full content.

Granillo, Yvette – Homework 1 – Due: Sep 13 2005, 3:00 am – Inst: Edward Odell 1 This print-out should have 25 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Simplify the difference quotient f ( x + h ) - f ( x ) h , ( h 6 = 0) , as much as possible when f ( x ) = 3 x 2 + 6 x - 13 . 1. 6 x + 6 + 3 h correct 2. 6 x - 6 + 3 h 3. 3 x - 6 + 3 h 4. 6 x + 6 5. 3 x + 6 + 3 h Explanation: Now f ( x + h ) = 3( x + h ) 2 + 6( x + h ) - 13 = 3 x 2 + 6 xh + 6 x + 3 h 2 + 6 h - 13 , while f ( x ) = 3 x 2 + 6 x - 13 . Thus f ( x + h ) - f ( x ) = 6 xh + 3 h 2 + 6 h . Consequently, f ( x + h ) - f ( x ) h = 6 x + 6 + 3 h . 002 (part 1 of 2) 10 points There is a linear relationship T F = mT C + b between the temperature T F on the Fahren- heit scale and its equivalent T C on the Centi- grade scale. As the thermometers 32 212 0 100 Freezing Boiling Farenheit Centigrade show, water freezes at 32 F and boils at 212 F, whereas it freezes at 0 C and boils at 100 C. Determine the relationship between T c and T F 1. T F = 5 9 T C + 32 2. T F = 5 9 T C - 32 3. T F = 9 5 T C + 32 correct 4. T F = 9 5 T C - 32 5. T C = 9 5 T F + 32 Explanation: Since water freezes at 32 F and at 0 C, T C = 0 = T F = 32 in the linear equation T F = mT C + b , so b = 32. On the other hand, since water boils at 212 F and at 100 C, T C = 100 = T F = 212; i.e. , 212 = 100 m + 32, so m = 9 5 . Conse- quently, T F = 9 5 T C + 32 .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Granillo, Yvette – Homework 1 – Due: Sep 13 2005, 3:00 am – Inst: Edward Odell 2 003 (part 2 of 2) 10 points Convert 5 C to its Fahrenheit equivalent. 1. 5 C 39 F 2. 5 C 38 F 3. 5 C 42 F 4. 5 C 40 F 5. 5 C 41 F correct Explanation: Substituting for T C = 5 in T F = 9 5 T C + 32 , we see that 5 C is equivalent to 9 + 32 F. Hence 5 C 41 F. 004 (part 1 of 1) 10 points Find the function g that results after the following transformations are applied in the order given to the graph of a function f : (1) stretch along y -axis by a factor 3; (2) reflect about the x -axis; (3) shift down 2 units; (4) reflect about the y -axis. 1. g ( x ) = - 2 - 3 f ( - x ) correct 2. g ( x ) = 6 - 2 f ( - x ) 3. g ( x ) = 6 + 3 f ( - x ) 4. g ( x ) = 3 f ( x ) - 6 5. g ( x ) = 6 - 3 f ( x ) Explanation: Beginning with a function y = f ( x ), the four transformations change f ( x ) as follows: f ( x ) (1) -→ 3 f ( x ) (2) -→ - 3 f ( x ) (3) -→ - 2 - 3 f ( x ) (4) -→ - 2 - 3 f ( - x ) . Consequently, g ( x ) = - 2 - 3 f ( - x ) . 005 (part 1 of 1) 10 points If f ( x ) = x 2 , which one of the following is the graph of the function g defined by g ( x ) = - f ( x - 1) + 2 ? 1. -4 -3 -2 -1 1 2 -1 1 2 3 4 5 6 7 2. -1 1 2 3 4 5 -1 1 2 3 4 5 6 7 3.
Granillo, Yvette – Homework 1 – Due: Sep 13 2005, 3:00 am – Inst: Edward Odell 3 -2 -1 1 2 3 4 -3 -2 -1 1 2 3 correct 4. -2 -1 1 2 3 4 -1 1 2 3 4 5 6 7 5. -2 -1 1 2 3 4 -1 1 2 3 4 5 Explanation: The graph of f ( x ) = x 2 is a parabola open- ing upwards and passing through the origin. To obtain the graph of the function g ( x ) = - f ( x - 1) + 2 from the graph of the function f ( x ) = x 2 , therefore, we perform the following transfor- mations on the graph of f : Shift it 1 unit(s) to the right; reflect the obtained graph over the x -axis; finally, shift the graph 2 units up.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 12

hw1 - Granillo Yvette Homework 1 Due 3:00 am Inst Edward...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online